OPTIMALISASI METODE INKUIRI DALAM MENINGKATKAN MINAT DAN HASIL BELAJAR SENI TARI TRADISIONAL PADA SISWA SMP NEGERI 3 SUKAWATI TAHUN AJARAN 2025/2026 - Gusti Ayu Made Puspawati; Komang David Darmawan; I Ketut Lanus (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to optimize the implementation of the inquiry method in improving students’ interest and learning outcomes in traditional dance at SMP Negeri 3 Sukawati in the 2025/2026 academic year. The background of this research is based on the low level of student interest and suboptimal learning outcomes caused by conventional teacher-centered learning approaches. This study employed a Classroom Action Research (CAR) design conducted in two cycles, consisting of planning, action, observation, and reflection stages. The research subjects were 32 eighth-grade students. Data were collected through observation, questionnaires on learning interest, and learning outcome tests. The results showed that the implementation of the inquiry method significantly improved students’ learning interest, as indicated by increased participation, curiosity, and active involvement in the learning process. In addition, students’ learning outcomes also improved, as reflected in the increase in the average scores and the percentage of learning mastery from the first to the second cycle. The inquiry method provides opportunities for students to explore, discover, and understand traditional dance movements more meaningfully. In conclusion, the optimization of the inquiry method is effective in enhancing both students’ interest and learning outcomes in traditional dance learning. This study is expected to contribute as an innovative and contextual learning strategy in cultural arts education, particularly in traditional dance learning at the junior high school level